DEVELOPMENT OF WIRELESS ELECTRICAL RESISTANCE TOMOGRAPHY - ABDUL KADIR, MOHD SAIFUL AKMAL (2018)
Internet of Things (IoT) has been the main venture in today’s industry whether it is currently applied or still in research. This also includes the investment on cloud computing, servers, autonomous robots and artificial intelligence (AI) in achieving Industry 4.0 where everything is more likely to be wireless and least human factor is implied. Industry 4.0 is now a benchmark to define the level of technology breakthrough and sophistication of a certain country. However, Malaysia is yet to achieve that.